Pemetaan Masalah Dalam Implementasi Kebijakan Rehabilitasi Penyalahguna Narkotika Di Indonesia - Ramdlonaning, Anisya; Natalud, Christian; Istyawan, Martha; Ayuningtyas, Vallendiah (UI Scholars Hub, 2022)
Indonesian government has some regulations that related to the Rehabilitation Policy for narcotics abusers. Unfortunately, the results are still not as expected. Many problems were found in its implementation, one of them is overcapapcity and overcrwoded at prison due to narcotics convicts or abusers. The other hand the number of abusers who access and receive rehabilitation services at rehabilitation institutions are limited. This study aims to map the problems that occur in the implementation of rehabilitation policies in Indonesia through a qualitative approach using the method of literature review within the framework of input, process, output and outcome logic models. Keywords: Policy Issues, Rehabilitation, Abuses, Drugs